Interpreting sanctions in Africa and Southeast Asia. (September 2015) - Hellquist, Elin
The Organization of African Unity (OAU) and the Association of Southeast Asian Nations (ASEAN) were both born to stabilise vulnerable state borders by practising non-interference in domestic affairs. Today, the OAU's successor, the African Union (AU), uses sanctions against unconstitutional changes of government, while ASEAN continues to rule out any collective punitive action against members. To explain these divergent trajectories, this article first shows how different traditions produced different ways of engaging with sanctions in the early formative cases of South Africa and Vietnam. Thereafter, it examines how these traditions were selectively re-thought when confronted with the dilemmas of international sanctions against Libya and Myanmar. The interpretive approach enables a nuanced account of continuity and change in beliefs about sanctions. The AU's sanctions doctrine has updated rather than broken with a traditional interpretation of non-interference. For ASEAN, the longstanding tradition of informality – and not strict adherence to non-interference – has continued to rule out regional sanctions.